Сучасні виклики та майбутнє правового захисту персональних даних: під впливом розвитку цифровізації - Дуравкін, П. М.; Гафич, І. І. (НДІ ПЗІР НАПрН України, 2023)
Стаття присвячена розгляду майбутніх викликів та можливостей, пов’язаних із захистом персональних даних. З високим розвитком технологій та збільшенням обсягу даних, конфіденційність та безпека персональних даних опиняються під загрозою. Кіберзлочинність та хакерські атаки зростають, вимагаючи посилення кібербезпекових стратегій. Глобалізація та перетин кордонів ускладнюють захист даних через різні правові норми. Однак, розвиток правових норм та регуляторів, таких як General Data Protection Regulation (GDPR), відкриває можливості для покращення захисту. Розумні технології та інновації, такі як блокчейн та шифрування, можуть забезпечити більшу безпеку та контроль над даними. Майбутнє захисту персональних даних залежатиме від спільних зусиль урядів, організацій та технологічних розробників у забезпеченні балансу між приватністю та використанням даних для інновацій та розвитку суспільства. Захист персональних даних вимагає спільних зусиль та співпраці між державними органами, приватним сектором та громадянським суспільством. Розробка міжнародних стандартів та правових норм, спрямованих на захист персональних даних, є важливим кроком на шляху до створення єдиного набору принципів та стандартів. Ми стикаємося з новими, безпрецедентними викликами, які не можуть бути вирішені простим розширенням старих норм і методів. Таким чином, необхідно розробляти та впроваджувати нові правові конструкції, а також долучатися до формування нових універсальних стандартів інформаційних прав людини. Однак, враховуючи сучасні світові тенденції необмеженого збору та використання персональної інформації, зростає ризик для права на захист персональних даних, яке, не встигнувши бути належним чином врегульованим на глобальному рівні, може зникнути. Таким чином, важливим завданням є визначення компромісних варіантів правового регулювання, які б, з одного боку, враховували всі вищезазначені аспекти, а з іншого – відповідали закономірностям розвитку суспільства, економіки та технологій. Автори дійщли висновку, що необхідно на нормативному рівні визначити перелік та механізми набуття цифрових прав, їх реалізації, захисту, компенсації та відповідальності за їх порушення. Одним із цифрових прав людини і громадянина слід вважати захист персональних даних. Розвиток цифровізації у правовій державі неминуче має супроводжуватися розвитком правової бази, зокрема, виникненням, закріпленням, визначенням та захистом цифрових прав фізичних та юридичних осіб. Багатогранність категорії «цифрові права» передбачає виокремлення та розмежування різних категорій цифрових прав, їх розподіл на відповідні види, наприклад, «особисті цифрові права», «фінансові цифрові права» тощо. Цілком закономірним має бути формування окремого елементу в загальній системі права, такого як цифрове право, як сукупності правових норм, що регулюють суспільні відносини, пов’язані з обігом (у тому числі персональних) даних у цифрових мережах. Problem setting. In order to build an innovative society, it is necessary to develop legal norms and regulators aimed at protecting privacy and controlling personal data. In addition, the need to ensure effective and reliable protection of personal data in the conditions of rapid technological development, globalization and the growing threat of cybercrime is becoming more urgent. The need for the development of legal norms, the introduction of innovative technologies and the raising of public awareness become important tasks for ensuring privacy and protection of personal data. The study also aims to identify and analyze the main challenges facing the field of personal data protection, such as cybercrime, hacker attacks, globalization and cross borders. Legal norms and regulations aimed at protecting privacy are also analyzed, as well as the potential opportunities of new technologies that can increase the level of protection of personal data. Аnalysis of recent researches and publications. The problems of legal protection of personal data have recently become the subject of research by an increasing number of scientists, both lawyers and representatives of other fields of knowledge. In particular, such scientists as: S. Hlibko, T. Egorova-Lutchenko, K. Yefremova, O. Korvat, V. Kokhan, M. Haustova devote their attention to the study of these issues. etc. Purpose of the research is to develop possible ways of legal protection of personal data in view of today’s challenges related to this issue. The article aims to consider the development of technologies and the growth of the volume of personal data as the main factors affecting the need for effective protection of privacy and security of this data. The article is aimed at expanding the understanding of the problem and providing recommendations for improving the protection of privacy and security of personal data in the future. article’s main body. According to the preamble to the Agreement between Ukraine and the European Union on the participation of Ukraine in the European Union program “Digital Europe” (2021-2027), the important supporting role of digital infrastructure, including in the field of cyber security, is recognized to ensure inextricably linked transformation processes and digital leadership of the European Union. The purpose of concluding the Agreement is to establish mutually beneficial cooperation in order to strengthen and support the deployment of reliable and secure digital capabilities in the Union in the field, including cyber security. It is recognized that mutual participation in each other’s programs for the implementation of digital technologies should ensure mutual benefits for the Parties, while observing a high level of data protection, digital rights, etc. In accordance with paragraph 12 of Article 2 of Annex III to the Agreement, the exchange of information between the European Commission or OLAF and the competent state authorities of Ukraine must take place with due consideration of confidentiality requirements. Personal data included in the exchange of information must be transferred in accordance with the current legal norms on data protection of the Party making the transfer. According to paragraph 49 of the preamble of Regulation (EU) 2021/694 of the European Parliament and of the Council of April 29, 2021 on the establishment of the Digital Europe Program, digital transformation should allow citizens to access, use and securely manage their personal data across borders, regardless of their location or data location. According to point 60 of the preamble, by providing a single set of rules that are directly applicable in the legal systems of the Member States, Regulation (EU) 2016/679 guarantees the free flow of personal data between Member States and strengthens the trust and security of individuals, two indispensable elements of a true Digital Single Market . All actions taken within the framework of the Program, which involve the processing of personal data, must contribute to the smooth implementation of this Regulation, for example, in the field of artificial intelligence and distributed ledger technologies (for example, blockchain). These actions should support the development of digital technologies that meet data protection obligations both by design and by default. In addition, according to paragraph 69 of the preamble, this Regulation respects fundamental rights and adheres to the principles recognized in the Charter of Fundamental Rights of the European Union, in particular regarding the protection of personal data, etc. In the Charter of Fundamental Rights of the European Union (2016/C 202/02) dated June 7, 2016, Chapter II “Freedoms” contains Article 8, which is entitled “Protection of personal data”, according to which it is assumed that everyone has the right to the protection of personal data data concerning him. Such data must be processed fairly for specific purposes and on the basis of the consent of the person concerned or on another legal basis established by law. Everyone has the right to access the data that has been collected about him and the right to correct it. Compliance with these rules is subject to control by an independent body. In addition, Regulation (EU) 2016/679 of the European Parliament and of the Council of April 27, 2016 on the protection of natural persons with regard to the processing of personal data and on the free movement of such data establishes rules relating to the protection of natural persons with regard to the processing of personal data, as well as rules, relating to the free movement of personal data, and protects the fundamental rights and freedoms of natural persons and, in particular, their right to protection of personal data. Today in Ukraine, the main legislative act in this area is the Law of June 1, 2010 No. 2997-VI “On the Protection of Personal Data”. Article 11 of the Law of Ukraine “On Information” specifies what information about a natural person (personal data) is. In turn, the legal and organizational bases for ensuring the protection of the vital interests of a person and citizen, society and the state, national interests of Ukraine in cyberspace, the main goals, directions and principles of state policy in the field of cyber security, the powers of state bodies, enterprises, institutions, organizations, individuals and citizens in this area, the basic principles of coordination of their cyber security activities are defined in the Law of Ukraine “On Basic Principles of Cyber Security of Ukraine”. In addition, relations in the field of information protection in information, electronic communication and information and communication systems are regulated by the Law of Ukraine “On the Protection of Information in Information and Communication Systems”. In turn, the Concept of the development of e-governance in Ukraine, as well as the Law of Ukraine “On the National Informatization Program” defines e-governance. In addition, in 2021, the Law of Ukraine “On Public Electronic Registers” was adopted, which defines the State electronic platform for maintaining public electronic registers. On April 18, 2023, by a resolution of the Cabinet of Ministers of Ukraine, the Regulation on the information system “Software platform for the deployment and support of state electronic registers” was approved, as well as the Procedure for using the software “Software platform for the deployment and support of state electronic registers”. conclusions and prospects for the development. The protection of digital personal data requires the development of appropriate technical and regulatory tools, as well as judicial practice of prosecution for violations of the order of their use. It is possible to create a database or registry for private electronic/digital platforms, with the help of which or which would control their activities, including regarding the protection of personal data. At the same time, at the regulatory and legal level, it is necessary to provide that a mandatory condition for the creation and functioning of an Internet platform is its registration in such a database / such a register, and a mandatory condition for registration is confirmation of technical capabilities to ensure the protection of personal data of platform users. It is necessary to define at the regulatory level the list and mechanisms of acquisition of digital rights, their implementation, protection, compensation and responsibility for their violation. The protection of personal data should be considered one of the digital rights of a person and a citizen. The development of digitalization in a legal state must inevitably be accompanied by the development of the legal framework, in particular, the emergence, consolidation, definition and protection of digital rights of individuals and legal entities. Digital rights are a multifaceted category, they become connected and interwoven with other rights defined and established in the norms of different branches of law. The multifaceted nature of the “digital rights” category implies the separation and delimitation of various categories of digital rights, their distribution into appropriate types, for example, “personal digital rights”, “financial digital rights”, etc. It should be quite natural to form a separate element in the general system of law, such as digital law, as a set of legal norms regulating social relations related to the circulation of (including personal) data in digital networks.
Keywords: електронне урядування; захист персональних даних; права людини; кібербезпека; маркетплейс; приватність; e-government; information system; personal data protection; human rights; cyber security; marketplace; privacy; legal tech; FinTech; цифрова платформа; цифрові права; digital platform; digital rights